Pemanfaatan Instagram Sebagai Sarana Pemasaran Produk Binaan PKK Secara Digital - Tri Santoso; Ardian Dwi Praba; Syahriani; Sulistianto SW (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Empowerment and Family Welfare Movement (PKK) has a role in mobilizing the community to be active in development. The role of PKK women must be in harmony with the development of conditions and the increasing demands of the needs of the community, in line with the development of regional autonomy. This organization has various work programs, including carrying out mutual cooperation, reviewing the implementation of posyandu, inviting village cadres to increase creativity that has selling points, and so on. In this working group organization, mothers are provided with valuable skills such as making bags from plastic coffee waste or dish washing soap, making fertilizer for plants from household waste, and so on. From some of the skills mentioned earlier, they have not been able to market their products to the fullest. Seeing this problem, this community service activity was carried out in order to increase the skills of PKK administrators or members of the organization in terms of marketing the products they produce through the help of Instagram social media. Then the method of community service carried out is planning, preparation and evaluation. The techniques used in it are the explanation of the theory contained in the modules that have been distributed and practice on how to use the Instagram application as well as questions and answers about the material provided. This community service is carried out online using the zoom application and other supporting applications such as Instagram, Google Chrome, WhatsApp. In addition, this service uses pretest and posttest questionnaires to find out the results of this community service that has been carried out.